ANALISIS DAYA SAING EKSPOR JAHE INDONESIA DI PASAR INTERNASIONAL - Kresna Aris Rusnaldi; Wiludjeng Roessali; Suryani Nurfadillah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Ginger is a herbal plant commodity with a high potential for export activity among other types of herbal plants. This potential is an opportunity for Indonesian ginger commodities to have competitiveness at the world level. This study aims to analyze the comparative and competitive advantages of Indonesian ginger exports in the global market, as well as to analyze the development and projections of Indonesian ginger exports in the global market. The study was carried out from September 2021 to February 2022. The study used the Secondary Data Analysis method in the form of a time series in the form of data on Indonesian ginger exports to the global market for the period 2013 – 2020 which came from various sources such as the Central Statistics Agency (Badan Pusat Statistik/BPS), The Center for Agricultural Data and Information Systems, Ministry of Agriculture, and Trade Map, International Trade Center (ITC). The data analysis method uses Revealed Comparative Advantages (RCA) analysis to analyze the comparative advantages of Indonesian ginger exports in the global market, Export Competitiveness Index (ECI) analysis to analyze the competitive advantages of Indonesian ginger exports in the global market and trend analysis to answer export developments and projections of Indonesian ginger in the global market. The results showed that Indonesia's ginger exports to the global market in 2013 - 2020 with an analysis of the RCA value showed an average value of 2.07 and an ECI of 0.92. The RCA value >1 indicates that Indonesian ginger has a comparative advantage in the global market but the ECI value <1 indicates that Indonesian ginger is competitively uncompetitive. The results of trend analysis and projections show that the export value of Indonesian ginger to the global market in 2013 - 2020 has a declining trend and the projection for the next 5 years is decreasing.